Low-temperature sodium-ion battery cathode material, preparation method and battery

By controlling the crystal plane size ratio and time-domain differential potential ratio of layered transition metal oxide cathode materials, the thermodynamic and kinetic properties of sodium-ion battery cathode materials are optimized, solving the problem of low capacity retention in sodium-ion batteries at low temperatures and achieving high capacity utilization under low-temperature conditions.

CN117613256BActive Publication Date: 2026-11-06XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311618365.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2026-11-06
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Existing sodium-ion battery cathode materials exhibit low capacity retention at low temperatures and slow sodium-ion diffusion, making it difficult to perform well in all weather conditions.

Method used

By controlling the crystal plane size ratio and time-domain differential potential ratio of layered transition metal oxide cathode materials, the thermodynamic and kinetic properties of the materials are optimized, and a sodium-ion battery cathode material suitable for low-temperature environments is prepared.

Benefits of technology

The capacity utilization of sodium-ion battery cathode materials is significantly improved under low-temperature conditions, and the performance of the materials in low-temperature environments is enhanced. The operation is simple and consumes few resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117613256B_ABST
    Figure CN117613256B_ABST
Patent Text Reader

Abstract

This invention provides a low-temperature sodium-ion battery cathode material, a preparation method thereof, and a sodium-ion battery. The cathode material is a layered transition metal oxide, and it satisfies condition (I) and / or condition (II). Condition (I) is: 1.6 ≤ K r ≤2.5, where d 210 The value of the 210 crystal plane in the XRD pattern of the cathode material represents the average grain size in the XRD pattern of the cathode material; condition (II) is: 5 ≤ K ΔV (T)≤10, where K ΔV (T) represents the time-domain differential potential ratio of the battery made with the aforementioned positive electrode material; m represents the adjustment coefficient, with a value ranging from 2 to 5; V0 represents the open-circuit potential of the battery measured at temperature T; V 1s This represents the potential value measured 1 second after the constant current is applied to the battery; V 16s This represents the potential value measured 16 seconds after the constant current is applied to the battery; the temperature T is 20–30°C. The cathode material meeting the above conditions exhibits a significant advantage in capacity utilization at low temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and particularly relates to a low-temperature sodium-ion battery positive electrode material, preparation method thereof, and battery. Background Art

[0002] Lithium-ion batteries have been gradually and widely applied in various industrial fields since 1991, and have developed rapidly in recent years. In addition to applications in 3C products such as mobile phones and notebook computers, the development of electric vehicles and smart grid energy storage has put forward new demands and technical requirements for secondary batteries. However, as the main raw material of lithium-ion batteries, lithium resources have limited reserves and uneven distribution. With the development of application fields of lithium-ion batteries, in the long run, the supply-demand relationship of lithium resources will gradually become intense and cannot meet the development demands. Therefore, it is particularly important to find the next-generation battery that can replace or partially replace lithium-ion batteries. Sodium element and lithium are both in Group 1 of the periodic table, have similar physical, chemical and electrochemical properties, and have much richer reserves. The working mechanism of sodium-ion batteries is similar to that of lithium-ion batteries, and can draw on the existing industrialization foundation of lithium batteries, so sodium-ion batteries are considered to be one of the best candidates for the next-generation secondary electrochemical batteries.

[0003] At present, the widely reported sodium-ion positive electrode materials mainly include the following types: 1. Layered transition metal oxide Na x TMO₂, 0<x<1, (TM represents transition metals and some other metal elements doped in the crystal lattice); 2. Polyanionic compounds (phosphates and the like); 3. Prussian blue; 4. Organic positive electrode materials. Among them, layered transition metal oxides have high theoretical capacity and structural stability, and are one of the highly potential positive electrode materials for sodium-ion batteries. However, current positive electrode materials for sodium-ion batteries are prone to form ordered structures and have low capacity retention. Moreover, since the ionic radius of sodium ions is much larger than that of lithium ions, they have the disadvantages of slow bulk diffusion rate and poor performance in extreme environments such as low-temperature environments. Therefore, how to solve the key problems of sodium-ion batteries under all-weather conditions has become a current difficulty.

[0004] It should be noted that the information disclosed in the above Background Art section is only for enhancing the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to a person of ordinary skill in the art. Summary of the Invention

[0005] To solve the above technical problems, the present invention provides a low-temperature sodium-ion battery positive electrode material, preparation method thereof, and battery.

[0006] According to a first aspect of the present invention, a low-temperature sodium-ion battery positive electrode material is provided, the positive electrode material is a layered transition metal oxide, and the positive electrode material satisfies condition (I) and / or condition (II): Condition (I): 1.6≤ ≤2.5, where, This indicates the crystal plane size ratio of the cathode material. , This indicates the 210 crystal plane size in the XRD pattern of the cathode material. This indicates the average grain size in the XRD pattern of the cathode material; Condition (II): 5≤ ≤10, where, This represents the time-domain differential potential ratio of the battery made with the aforementioned cathode material. , This represents the adjustment coefficient, with a value ranging from 2 to 5; This represents the open-circuit potential of the battery measured at temperature T; This represents the potential value measured 1 second after the constant current is applied to the battery; This indicates the potential value measured 16 seconds after the constant current is applied to the battery; the temperature T is 20~30℃.

[0007] In an exemplary embodiment of the invention, the positive electrode material satisfies: 1.9 ≤ ≤2.2, 6≤ ≤8.

[0008] In one exemplary embodiment of the invention, the The characteristic peaks representing the 210 crystal plane in the XRD pattern were obtained by refining and fitting the pattern using the Rietveld fitting refinement method. The XRD pattern was obtained by full-spectrum fitting using the Rietveld fitting refinement method; the XRD test conditions were: angle range: 10°-80°, step size 0.02Å, dwell time per step 0.3s.

[0009] In one exemplary embodiment of the invention, the general chemical formula of the positive electrode material is NaFe. x Ni y Mn z M 1-x-y-z O2, wherein 0 ≤ x < 0.35, 0 < y < 0.35, 0 ≤ z ≤ 0.35; element M is selected from at least one of P, F, Al, Ti, Zr, Co, Zn and Cu.

[0010] In one exemplary embodiment of the invention, NaFe x Ni y Mn z M 1-x-y-zIn O2, 0.30<x<0.35, 0.30<y<0.35, 0.30≤z≤0.35, 0.90≤x+y+z≤1.

[0011] In one exemplary embodiment of the invention, the time-domain differential potential ratio The steps to obtain it include: The positive electrode material is made into a positive electrode sheet, and the positive electrode sheet is assembled with a separator, a negative electrode and an electrolyte to obtain a coin cell. The coin cell was subjected to its first charge-discharge cycle at temperature T to obtain a test sample. The test sample was charged at a constant current rate of 0.1C to a cutoff voltage of 4.0V (vs Na), and then charged at a constant voltage rate of 4.0V (vs Na) to a cutoff rate of 0.02C. Discharge at a constant current rate of 0.1C to 3.47V (vs Na), then discharge at a constant voltage rate of 3.47V (vs Na) to a cutoff rate of 0.01C. Let it stand for 1 hour and record the actual open circuit potential value. ; A constant current pulse discharge was performed with a discharge rate of 1.0C and a pulse duration of 60 seconds. The instantaneous potential value at 1 second was recorded. Record the instantaneous potential value at 16 seconds, which is... ; according to Calculation, obtained .

[0012] According to a second aspect of the present invention, a method for preparing a low-temperature sodium-ion battery cathode material as described in any one of the above claims is provided, comprising: S1, prepare sodium source, transition metal source, additive containing element M, organic orientation regulator and sodium salt supplement as raw materials, mix the raw materials and water evenly to obtain a mixed solution; S2, the mixed solution is transferred to a reaction vessel, CO gas is introduced to a saturated concentration, the reaction vessel is sealed, and a hydrothermal reaction is carried out. After the reaction is completed, the precursor is separated. S3, the precursor is sintered to obtain the low-temperature sodium-ion battery cathode material.

[0013] In an exemplary embodiment of the invention, the sodium source is selected from one or more of sodium fluoride, sodium phosphate, sodium carbonate, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate; the transition metal source includes Ni oxide, Fe oxide, and Mn oxide; the additive is a soluble salt or oxide containing element M; the organic orientation modifier is a long-chain aliphatic amine compound; the mass fraction of the organic orientation modifier in the raw material is 1% to 10%; and the sodium source supplement is selected from soluble sodium salts.

[0014] In an exemplary embodiment of the invention, in step S2, the temperature of the hydrothermal reaction is 120~200℃ and the reaction time is 10~20 h; and / or, in step S3, the sintering temperature is 800~1000℃ and the sintering time is 8~16 h.

[0015] According to a third aspect of the present invention, a sodium-ion battery is provided, comprising the low-temperature sodium-ion battery cathode material as described in any of the preceding claims.

[0016] The beneficial effects of the low-temperature sodium-ion battery cathode material, preparation method, and battery of this invention are as follows: The capacity performance of sodium-ion battery cathode materials under low-temperature conditions is closely related to the structure and morphology of the cathode materials, especially for single-crystal or near-single-crystal materials. Due to the limitations of thermodynamics and kinetics in crystal growth, there is a certain inheritance between their macroscopic morphology and microscopic crystal structure. This invention addresses this by controlling the ratio of the 210 crystal plane size to the average grain size in the XRD pattern of the cathode material. The range of 1.6 to 2.5 allows the cathode material to exhibit a significant advantage in terms of capacity performance under low-temperature conditions, providing a feasible technical solution to overcome the problem of low capacity performance of sodium-ion battery cathode materials in low-temperature environments.

[0017] Furthermore, the low-temperature performance of sodium-ion battery cathode materials depends on both thermodynamic and kinetic factors. Thermodynamic factors are primarily related to the material's entropy change characteristics and low-temperature level. Kinetic factors, on the other hand, depend on the absolute polarization values ​​of each component of the battery during charging and discharging and their changes with temperature. The ratio of bulk and interfacial polarization in the cathode material affects the overall polarization level. Currently, no sodium-ion battery cathode material has considered this influence. In this embodiment of the invention, the time-domain differential potential ratio is obtained by controlling the cathode material at a temperature T (20~30℃) and an open-circuit potential (OCV) of 3.47V (vs Na) through galvanostatic chronopotential measurement. By regulating the change in polarization of the cathode material with temperature, the goal of improving the low-temperature capacity of the cathode material in sodium-ion batteries was achieved. The acquisition of it does not require a low-temperature environment, is simple to operate, and consumes few resources.

[0018] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this disclosure and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 The image shows the XRD pattern of the layered oxide cathode material obtained in Example 1 of this invention.

[0021] Figure 2 The room temperature time-domain differential potential ratio in Test Example 3 of this invention The relationship curve between low-temperature capacity retention rate and the low-temperature capacity retention rate. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions in the embodiments of this disclosure will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0023] The following provides a detailed description of the low-temperature sodium-ion battery cathode material, preparation method, and battery according to embodiments of the present invention.

[0024] This embodiment provides a low-temperature sodium-ion battery cathode material, wherein the cathode material is a layered transition metal oxide, specifically, the cathode material is a single crystal or near-single crystal layered transition metal oxide.

[0025] Furthermore, in one embodiment, the general chemical formula of the positive electrode material is NaFe. x Ni y Mn z M 1-x-y-z O2, where 0 ≤ x < 0.35, 0 < y < 0.35, 0 ≤ z ≤ 0.35; element M is selected from at least one of P, F, Al, Ti, Zr, Co, Zn, and Cu. By doping with different elements, more vacancies can be formed. Furthermore, 0.30 < x < 0.35, 0.30 < y < 0.35, 0.30 ≤ z ≤ 0.35, and 0.90 ≤ x + y + z ≤ 1.

[0026] In this embodiment, the positive electrode material satisfies condition (I) and / or condition (II): Specifically, condition (I): 1.6≤ ≤2.5, where, This indicates the crystal plane size ratio of the cathode material. , This indicates the 210 crystal plane size in the XRD pattern of the cathode material. This indicates the average grain size in the XRD pattern of the cathode material.

[0027] Specifically, in this embodiment of the invention, the XRD test of the above-mentioned cathode material was performed on a Bruker D8 ADVANCE instrument, using Cu-kα as the radiation source. The powder was poured into the sample holder using the upright loading method to ensure that the sample height was consistent with the sample holder; the sample testing conditions were: angle range: 10°-80°, step size 0.02 Å, and dwell time per step 0.3 s. The XRD pattern was then obtained.

[0028] Furthermore, the aforementioned The characteristic peaks representing the 210 crystal plane in the XRD pattern were obtained by refining and fitting the pattern using the Rietveld fitting refinement method. The XRD pattern was obtained by full-spectrum fitting using the Rietveld fitting refinement method. Specifically, the calculation steps for fitting refinement are as follows: (a): Open the TOPAS refinement software and import the tested XRD spectrum into the software; (b): Select the batch of samples that need to be refined, first perform background subtraction, select the background fitting parameter (Background) and change the polynomial series Order to 4; then import the instrument parameters in the instrument parameter (Instrument) task bar; check the Sample displacement (sample height correction) in the error correction parameter (Corrections). (c): Import the structure file of the sodium electrode cathode material. In the structure file, select Sites to set the structure parameters according to the material characteristics, perform full-spectrum fitting, and obtain the average grain size of the full-spectrum fitting. Then, the characteristic peak of the 210 crystal plane (approximately 62°) is selected for single-peak fitting to obtain the 210 crystal plane size d. 210 210 crystal plane size d 210 Characterizes the thickness of the unit cell perpendicular to the 210 crystal plane.

[0029] (d): Calculation and ratio ,in, .

[0030] Specifically, condition (II): 5≤ ≤10, where, This represents the time-domain differential potential ratio of the battery made with the aforementioned cathode material. , This represents the adjustment coefficient, with a value ranging from 2 to 5; This represents the open-circuit potential of the battery measured at temperature T; This represents the potential value measured 1 second after the constant current is applied to the battery; This indicates the potential value measured 16 seconds after the constant current is applied to the battery; the temperature T is 20~30℃.

[0031] Furthermore, in one embodiment, the temperature T is 25°C, and the temperature is set to room temperature. The time-domain differential potential ratio is measured in a room temperature environment, which is simple and convenient.

[0032] Furthermore, in one embodiment, the adjustment coefficient It can be 2, 3, 4, 5, etc., preferably, the adjustment coefficient. The value is 3. Using this adjustment coefficient can better characterize the bulk phase and interfacial polarization ratio of the cathode material.

[0033] Furthermore, in one embodiment, the time-domain differential potential ratio The steps to obtain it include: (1) The positive electrode material is made into a positive electrode sheet, and the positive electrode sheet is assembled with a separator, a negative electrode and an electrolyte to obtain a button cell.

[0034] (2) The coin cell battery is subjected to its first charge and discharge at temperature T to obtain a test sample. Specifically, the first charge and discharge is performed at room temperature of 25°C. Specifically, the first charge and discharge process can be as follows: at 25°C, it is charged at a constant current rate of 0.1C to 4.0V (vs Na), charged at a constant voltage at 4.0V (vs Na) to the cutoff rate of 0.02C, and discharged at a constant current rate of 0.1C to 2.0V (vs Na).

[0035] (3) Charge the test sample at a constant current at a rate of 0.1C to the cutoff voltage of 4.0V (vs Na), and then charge it at a constant voltage at a potential of 4.0V (vs Na) to the cutoff rate of 0.02C; (4) Discharge at a constant current rate of 0.1C to 3.47V (vs Na), then discharge at a constant voltage rate of 3.47V (vs Na) to a cutoff rate of 0.01C. Let it stand for 1 hour and record the actual open circuit potential value, which is the open circuit potential value. ; (5) Set the discharge rate to 1.0C and perform constant current pulse discharge. The pulse duration is 60 seconds. Record the instantaneous potential value at 1 second, which is the value of the discharge. Record the instantaneous potential value at 16 seconds, which is... ; (6) According to Calculation, obtained .

[0036] The above process first involves performing a necessary initial specific capacity test on the battery, followed by pre-charging to a state of charge (SOC) of 100%. A combination of constant current discharge (CC step) and constant voltage discharge (CV step) is then used to control the potential to 3.47V (vsNa). , and The measurement can be performed on a battery electrical performance tester with a potential accuracy of 0.3mV, specifically during the discharge phase.

[0037] Furthermore, in the above-mentioned acquisition step (1), the coin cell belongs to a two-electrode electrolytic cell system. The coin cell can be prepared according to the methods in the existing technology. Specifically, commercially available coin cells such as CR2023, CR2025, and CR2016 can be used. The following uses CR2023 as an example to explain the preparation method of the coin cell. The preparation method of the CR2023 coin cell is as follows: Step a: The positive electrode uses aluminum foil as the current collector and the above-mentioned layered transition metal oxide as the positive electrode material. The positive electrode material (mass percentage controlled ≤ 94%), conductive agent (mass percentage controlled ≥ 3%), binder (mass percentage controlled ≥ 3%), and N-methylpyrrolidone (2,4) are mixed and prepared into a slurry in a degassing machine, controlling the viscosity of the slurry to be between 7000-9000 mPa·s. The slurry is then uniformly coated onto the aluminum foil using an automatic coating machine to form the primary electrode sheet. This sheet is then dried in a vacuum oven at 130℃ for 4 hours, and then placed in a forced-air oven at 80℃ for 12 hours to obtain the test sheet.

[0038] Step b: Use a punching die with a diameter of 14 mm to cut out several small electrode pieces at different positions of the above test piece. Select small electrode pieces with regular shape, flat surface and edges, weigh them with a balance of 0.001%, put the weighed small electrode pieces into a vacuum drying oven, evacuate to 0.1 MPa, and store them for later use.

[0039] Step c: Assemble the coin cell in an inert gas glove box containing 0.0005% or less water and oxygen by mass. The battery specification is CR2023, the separator is a polypropylene membrane, and the negative electrode is a sodium sheet. The electrolyte can be a mixture of organic carbonates, such as cyclic carbonates like ethylene carbonate (EC) and propylene carbonate (PC), and chain carbonates like dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC). In this embodiment, a 1:1 EC / DEC volume ratio mixture is used as the electrolyte. The conductive salt in the electrolyte is 1M sodium hexafluorophosphate. After assembly, the cells are encapsulated at a pressure of 800 Pa for 5 seconds. The resulting coin cell is then formed.

[0040] Furthermore, in one embodiment, the positive electrode material satisfies: 1.9 ≤ ≤2.2 and satisfy 6≤ ≤8. When the crystal plane size of the cathode material is greater than... and time-domain differential potential ratio Maintaining this range can further improve the capacity performance of the cathode material under low-temperature conditions.

[0041] This invention also provides a method for preparing the above-mentioned low-temperature sodium-ion battery cathode material, comprising: S1, prepare sodium source, transition metal source, additive containing element M, organic orientation regulator and sodium salt supplement as raw materials, mix the raw materials and water evenly to obtain a mixed solution; S2, the mixed solution is transferred to a reaction vessel, CO gas is introduced to a saturated concentration, the reaction vessel is sealed, and a hydrothermal reaction is carried out. After the reaction is completed, the precursor is separated. S3, the precursor and sodium salt supplement are mixed and then sintered to obtain the low-temperature sodium-ion battery cathode material.

[0042] The above preparation method uses a hydrothermal reaction to prepare the precursor, and adds an organic orientation modifier during this process to control the crystal orientation of the cathode material. Simultaneously, saturated carbon monoxide gas is introduced during the hydrothermal reaction to increase the internal pressure. The different adsorption capacities of CO gas on different crystal orientations allow it to work with the organic orientation modifier to regulate crystal growth during the hydrothermal reaction, thereby achieving the desired crystal orientation of the cathode material. and Effective control of the value leads to the production of low-temperature resistant sodium-ion cathode materials.

[0043] Further, in step S1, the sodium source is selected from one or more of sodium fluoride, sodium phosphate, sodium carbonate, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate. For example, the sodium source is sodium fluoride or sodium phosphate. Further, the concentration of the sodium source in the mixed solution is 1~10 mol / L, for example, 1 mol / L, 4 mol / L, 8 mol / L, etc.

[0044] Further, in step S1, the transition metal source includes Ni oxide, Fe oxide, and Mn oxide. Further, the ratio of Ni oxide, Fe oxide, and Mn oxide can be determined according to the chemical formula NaFe. x Ni y Mn z M 1-x-y-z O2 is provided as a backup. For example, the amounts of Ni oxide, Fe oxide, and Mn oxide are in a molar ratio of Ni:Fe:Mn = 1:1:1. For example, the transition metal source is iron oxide, nickel oxide, and manganese oxide.

[0045] Further, in step S1, the additive is a soluble salt or oxide containing element M. The soluble salt can be a chloride, sulfate, oxalate, carbonate, nitrate, etc. For example, the additive may be aluminum chloride, titanium oxalate, cobalt sulfate, zinc chloride, copper sulfate, zirconium sulfate, phosphorus pentoxide, etc.

[0046] Further, in step S1, the organic orientation modifier is a long-chain aliphatic amine compound; the mass fraction of the organic orientation modifier in the raw material is 1% to 10%. More preferably, the mass fraction of the organic orientation modifier is 1% to 5%, for example, 1%, 2%, 5%, etc. Further, the organic orientation modifier can be selected from one or more of dodecylamine, hexadecylamine, heptadecanamine, octadecylamine, etc.

[0047] Furthermore, in step S1, the raw materials and pure water are thoroughly ground in a sand mill to ensure that the components are mixed evenly and a mixed solution is obtained.

[0048] Further, in step S1, the sodium salt supplement can be a water-soluble sodium salt compound. For example, the sodium salt supplement can be selected from one or more of sodium oxalate, sodium bicarbonate, and sodium citrate. The amount of sodium salt supplement is determined as follows: the molar ratio of Na element (including the amount of sodium source added in step S1 and the amount of sodium salt supplement added in step S1) to transition metal elements (the sum of Ni, Fe, and Mn) is 1.0~1.1:1.

[0049] Further, in step S2, the hydrothermal reaction temperature is 120~200℃, and the reaction time is 10~20 h. More preferably, the hydrothermal reaction temperature is 140~180℃, and the reaction time is 10~14 h. Under these parameter conditions, the hydrothermal reaction can improve the integrity and structural stability of the precursor crystal structure, and further improve the capacity performance of the cathode material.

[0050] Further, in step S2, after the hydrothermal reaction is completed, the temperature is lowered to room temperature, the reaction vessel is opened and the mixture containing the precursor is taken out, the precipitate is collected by centrifugation in a centrifuge at 6000 rpm, and washed twice with 80% ethanol aqueous solution to obtain the corresponding precursor precipitate. The precipitate is dried in a vacuum oven at 60°C and a vacuum degree of less than 100 Pa for 24 hours to obtain the precursor.

[0051] Further, in step S3, the sintering temperature is 800~1000℃, and the sintering time is 8~16 h. More preferably, the sintering temperature is 850~950℃, and the sintering time is 11~13 h. The sintering process is carried out in an oxygen atmosphere or an air atmosphere.

[0052] This invention also provides a sodium-ion battery, comprising: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the aforementioned low-temperature sodium-ion battery positive electrode material. The sodium-ion battery may further include a separator between the positive and negative electrodes. It is understood that sodium-ion batteries can be prepared according to known methods in the prior art, and will not be described in detail in this invention.

[0053] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0054] Examples 1-5

[0055] This embodiment provides a layered oxide cathode material, obtained by the following steps: (1) Prepare the raw materials according to the proportions in Table 1. The raw materials include: Na source, iron oxide, nickel oxide, manganese dioxide, additives, organic orientation modifier, and sodium salt supplement. Among them, iron oxide, nickel oxide, and manganese dioxide are prepared according to the molar ratio of Ni, Fe, and Mn of 1:1:1. The Na source is prepared according to the molar ratio of Na to (Fe+Ni+Mn) of 1:1. Grind the raw materials and pure water thoroughly in a sand mill and mix them evenly to obtain a mixed salt solution. The sodium salt supplement is prepared according to the molar ratio of the total Na to the total transition metals of 1.05~1:1.

[0056] (2) Pour each mixed solution into a hydrothermal reactor, and then introduce carbon monoxide gas until the concentration reaches saturation or do not introduce carbon monoxide gas. Immediately seal the reactor and place it in an oven at 160°C for 12 hours to carry out the hydrothermal reaction. After the reaction is complete, cool it to room temperature, open the reactor and take out the mixed solution containing the precursor. Centrifuge at 6000 rpm to collect the precipitate, and wash it twice with 80% ethanol aqueous solution to obtain the corresponding precursor precipitate. Dry it in a vacuum oven at 60°C under a vacuum of less than 100 Pa for 24 hours to obtain the precursor powder.

[0057] (3) The precursor powder obtained in step (2) is placed in a tube furnace and sintered at 900°C for 12 h in an oxygen atmosphere. After cooling, the corresponding layered oxide cathode material can be obtained, which are samples of Examples 1 to 5 respectively.

[0058] Table 1 Sample number Na source Additives and their mass fraction in raw materials Organic orientation modifiers and their mass fraction in raw materials carbon monoxide Sodium supplements Molar ratio of total Na to total transition metals Example 1 Sodium fluoride Aluminum chloride (0.5%), titanium oxalate (0.1%), cobalt sulfate (1%), zinc chloride (1%) Octadecylamine (1%) Carbon monoxide (saturated) Sodium citrate (1.05g) 1.05:1 Example 2 Sodium phosphate Aluminum chloride (0.5%), zirconium oxalate (0.1%), copper sulfate (1%), zinc chloride (1%) Hexadecylamine (2%) Carbon monoxide (saturated) Sodium oxalate (1.05g) 1.05:1 Example 3 Sodium phosphate Aluminum chloride (0.5%), zirconium oxalate (0.1%), copper sulfate (1%), zinc chloride (1%) Hexadecylamine (5%) Carbon monoxide (saturated) Sodium citrate (1.1) 1.1:1 Example 4 Sodium fluoride Aluminum chloride (0.5%), titanium oxalate (0.1%), cobalt sulfate (1%), zinc chloride (1%) Octadecylamine (1%) none Sodium citrate 1.05:1 Example 5 Sodium phosphate Aluminum chloride (0.5%), zirconium oxalate (0.1%), copper sulfate (1%), zinc chloride (1%) none Carbon monoxide (saturated) none 1:1 Test Example 1: Crystal Facet Size Ratio Test The layered oxide cathode materials obtained in Examples 1-5 were subjected to XRD testing according to the method provided above. The XRD testing conditions were: angle range: 10°-80°, step size: 0.02 Å, and dwell time per step: 0.3 s.

[0059] Example 1 will be used as an example for illustration, such as Figure 1 The image shows the XRD pattern of the layered oxide cathode material prepared in Example 1. The characteristic peak of the 210 crystal plane is approximately 62°. Following the method described above, the XRD pattern was refined and fitted, and the characteristic peak of the 210 crystal plane was fitted as a single peak to obtain the grain size of the 210 crystal plane. The average grain size was obtained by fitting the full spectrum. According to the formula Calculated The test results are shown in Table 2 below: Table 2

[0060] Test Example 2: Time Domain Differential Potential Ratio Test Using the layered oxide cathode materials prepared in Examples 1-5 as the cathode materials for sodium-ion batteries, CR2023 coin cells were assembled according to the preparation method described above. The mass ratio of the cathode material to the conductive agent Super P and the binder PVDF was 9:0.14:0.2, the anode was a sodium sheet, the separator was a polypropylene membrane, the electrolyte solvent was a 1:1 volume ratio mixture of EC and DEC, and the conductive salt was 1M sodium hexafluorophosphate.

[0061] The obtained coin cells, labeled as Sample A (Example 1), Sample B (Example 2), Sample C (Example 3), Sample D (Example 4), and Sample E (Example 5), were subjected to time-domain differential potential ratio testing. The testing process is illustrated using Sample A as an example: First, sample A underwent a necessary initial charge-discharge cycle, followed by pre-charging to 100% state of charge (SOC). Specifically, at 25°C, it was charged at a constant current rate of 0.1C to 4.0V (vs Na), then charged at a constant voltage rate of 4.0V (vs Na) to a cutoff rate of 0.02C, and finally discharged at a constant current rate of 0.1C to 2.0V (vs Na). At 25°C, the discharge phase was measured using a battery performance testing instrument with a potential accuracy of 0.3mV, as detailed below: At room temperature (25℃), sample A was charged at a constant current rate of 0.1C to a cutoff voltage of 4.0V (vs Na), and then charged at a constant voltage rate of 4.0V (vs Na) to a cutoff rate of 0.02C. It was then discharged at a constant current rate of 0.1C to 3.47V (vs Na), and then discharged at a constant voltage rate of 3.47V (vs Na) to a cutoff rate of 0.01C. After standing for 1 hour, the actual open-circuit potential value was recorded. Set the discharge rate to 1.0C and perform constant current pulse discharge for 60 seconds. Record the instantaneous potential value at 1 second; this is the voltage. Record the instantaneous potential value at 16 seconds, which is... .

[0062] According to the formula Calculate the time-domain differential potential ratio of sample A. The calculation results are shown in Table 3.

[0063] Table 3

[0064] Test Example 3: Low Temperature Capacity Test Coin cells were prepared using the same method as in Test Example 2. Each cell was labeled as Sample A' (Example 1), Sample B' (Example 2), Sample C' (Example 3), Sample D' (Example 4), and Sample E' (Example 5), and time-domain differential potential ratio was tested. The testing process is illustrated using Sample A' as an example: Low-temperature capacity testing was performed using a battery electrical performance tester with a potential accuracy of 0.3mV. The testing process followed these steps.

[0065] (1) At 25°C, charge at a constant current of 0.1C to 4.0V (vs Na), charge at a constant voltage of 4.0V (vs Na) to the cutoff rate of 0.02C, and discharge at a constant current of 0.1C to 2.0V (vs Na).

[0066] (2) At 25°C, charge at a constant current rate of 0.1C to 4.0V (vs Na), and charge at a constant voltage at 4.0V (vs Na) until the current drops to 0.02C; (3) Let stand for 4 hours, then cool to -20℃ and let stand for 4 hours; (4) At -20℃, the discharge rate is constant current discharge at 0.1C to 2.0V (vs Na), and the discharge specific capacity at -20℃ is measured to be Q2, and the capacity retention rate is Q2 / Q1.

[0067] (5) Let stand for 1 hour, then raise the temperature to 25°C and let stand for 1 hour; (6) At 25°C, charge at a constant current rate of 0.1C to 4.0V (vs Na), and charge at a constant voltage at 4.0V until the current drops to 0.02C; (7) Let stand for 4 hours, then cool to -30℃ and let stand for 4 hours; (8) At -30℃, the discharge rate is constant current discharge at 0.1C to 2.0V (vs Na), and the discharge specific capacity at -30℃ is measured to be Q3, and the capacity retention rate is Q3 / Q1.

[0068] (9) Let stand for 1 hour, then raise the temperature to 25°C and let stand for 1 hour; (10) At 25°C, charge at a constant current rate of 0.1C to 4.0V (vs Na), and charge at a constant voltage at 4.0V (vs Na) until the current drops to 0.02C; (11) After standing for 4 hours, at 25°C, the discharge rate was constant at 0.1C to 2.0V (vs Na), and the discharge specific capacity at 25°C was measured to be Q1.

[0069] The test results are shown in Table 4.

[0070] Table 4

[0071] like Figure 2 The figure shows the time-domain differential potential ratio at room temperature. The relationship curve between the low-temperature capacity retention rate and the low-temperature capacity retention rate. As can be seen from the above test examples 1-3, the low-temperature capacity of the samples in Examples 4 and 5 is poor, and their crystal plane size is... The values ​​were 1.593 and 2.502, respectively, with time-domain differential potential ratios of 9.8 and 4.9. The capacities of the three samples from Examples 1-3 at -20°C remained above 80% of their capacities at room temperature, and their crystal plane size ratios were... The values ​​are 1.864, 1.987, and 2.194, respectively; room temperature time-domain differential potential ratio. The values ​​are 8.3, 7.4, and 6.1, respectively. Therefore, for single-crystal or near-single-crystal layered transition metal oxide cathode materials suitable for sodium-ion batteries, when... and When maintained within a suitable range, the capacity performance of cathode materials is better under low-temperature conditions.

[0072] The above description does not cover all embodiments. The detailed description of embodiments in this disclosure is not intended to limit the scope of the claimed disclosure, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments in this disclosure without inventive effort are within the scope of protection of this disclosure.

Claims

1. A low-temperature sodium-ion battery cathode material, characterized in that, The cathode material is a layered transition metal oxide, and the cathode material satisfies conditions (I) and (II): Condition (I): 1.6≤ ≤2.5, where, This indicates the crystal plane size ratio of the cathode material. , This indicates the 210 crystal plane size in the XRD pattern of the cathode material. This represents the average grain size in the XRD pattern of the cathode material, and the 210 crystal plane size d. 210 Characterizes the thickness of the unit cell perpendicular to the 210 crystal plane; Condition (II): 5≤ ≤10, where, This represents the time-domain differential potential ratio of the battery made with the aforementioned cathode material. , This represents the adjustment coefficient, with a value ranging from 2 to 5; This represents the open-circuit potential of the battery measured at temperature T; This represents the potential value measured 1 second after the constant current is applied to the battery; This represents the potential value measured 16 seconds after the constant current is applied to the battery; the temperature T is 20~30℃. The general chemical formula of the positive electrode material is NaFe. x Ni y Mn z M 1-x-y-z O2, wherein 0 ≤ x < 0.35, 0 < y < 0.35, 0 ≤ z ≤ 0.35; element M is selected from at least one of P, F, Al, Ti, Zr, Co, Zn and Cu.

2. The low-temperature sodium-ion battery cathode material according to claim 1, characterized in that, The positive electrode material satisfies: 1.9 ≤ ≤2.2, 6≤ ≤8.

3. The low-temperature sodium-ion battery cathode material according to claim 1, characterized in that, The The characteristic peaks representing the 210 crystal plane in the XRD pattern were obtained by refining and fitting the pattern using the Rietveld fitting refinement method. The XRD pattern was obtained by full-spectrum fitting using the Rietveld fitting refinement method; the XRD test conditions were: angle range: 10°-80°, step size 0.02Å, dwell time per step 0.3s.

4. The low-temperature sodium-ion battery cathode material according to claim 1, characterized in that, NaFe x It’s y Mn z M 1-x-y- z O2.0.30<x<0.35,0.30<y<0.35,0.30≤z≤0.35,0.90≤x+y+z≤1。 5. The low-temperature sodium-ion battery cathode material according to any one of claims 1 to 4, characterized in that, The time-domain differential potential ratio The steps to obtain it include: The positive electrode material is made into a positive electrode sheet, and the positive electrode sheet is assembled with a separator, a negative electrode and an electrolyte to obtain a coin cell. The coin cell was subjected to its first charge-discharge cycle at temperature T to obtain a test sample. The test sample was charged at a constant current rate of 0.1C to a cutoff voltage of 4.0V vs Na, and then charged at a constant voltage rate of 4.0V vs Na to a cutoff rate of 0.02C. Discharge at a constant current rate of 0.1C to 3.47V vs Na, then discharge at a constant voltage rate of 3.47V vs Na to a cutoff rate of 0.01C. Let it stand for 1 hour and record the actual open circuit potential value. ; A constant current pulse discharge was performed with a discharge rate of 1.0C and a pulse duration of 60 seconds. The instantaneous potential value at 1 second was recorded. Record the instantaneous potential value at 16 seconds, which is... ; according to Calculation, obtained .

6. A method for preparing a low-temperature sodium-ion battery cathode material according to any one of claims 1 to 5, characterized in that, include: S1, prepare sodium source, transition metal source, additive containing element M, organic orientation regulator and sodium salt supplement as raw materials, mix the raw materials and water evenly to obtain a mixed solution; S2, the mixed solution is transferred to a reaction vessel, CO gas is introduced to a saturated concentration, the reaction vessel is sealed, and a hydrothermal reaction is carried out. After the reaction is completed, the precursor is separated. S3, the precursor is sintered to obtain the low-temperature sodium-ion battery cathode material.

7. The preparation method according to claim 6, characterized in that, In step S1, the sodium source is selected from one or more of sodium fluoride, sodium phosphate, sodium carbonate, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate; the transition metal source includes Ni oxide, Fe oxide, and Mn oxide; the additive is a soluble salt or oxide containing element M; the organic orientation modifier is a long-chain aliphatic amine compound; the mass fraction of the organic orientation modifier in the raw material is 1% to 10%; and the sodium salt supplement is selected from water-soluble sodium salts.

8. The preparation method according to claim 6, characterized in that, In step S2, the hydrothermal reaction temperature is 120~200℃ and the reaction time is 10~20 h; and / or, in step S3, the sintering temperature is 800~1000℃ and the sintering time is 8~16 h.

9. A sodium-ion battery, characterized in that, Includes the low-temperature sodium-ion battery cathode material as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Metal ion doped modified sodium ion material as well as preparation method and application thereof

    CN114005969A

  • Low-nickel high-energy-density O3 type sodium ion battery positive electrode material and preparation method thereof

    CN116544408A